Internal environmental factors: An ordered Logit analysis of tourism business success - Sibusiso D. Ntshangase; Ikechukwu O. Ezeuduji (Acta Commercii)
Orientation: Research on tourism entrepreneurship often generalises findings from developed markets, overlooking the unique internal environmental factors and socio-economic contexts in emerging destinations.